An Analysis of the Implementation of Natural Disaster Tackling in Kota Palu - Dalanggo, Marwati; Kadir, Haris Abdul; Rahman, Abdul (Universitas Muhammadiyah Palu, 2021)
This research aims to find out the implementation of natural disaster tackling in Kota Palu by analyzing job performance at the Office of the local disaster tackling institute of Kota Palu. To measure the Office's job performance of the local catastrophe tackling institute of Kota Palu, some suitable aspects are used, namely productivity, service quality, responsiveness, responsibility, and accountability. Research findings show that those aspects are expected to become measuring the standard of valuation of job perfomance of the organization of the local disaster tackling institute of Kota Palu.